Epigenetics: Hereditary changes due to anxiolytics and antidepressants (Research, Society and Development, 2022)
Epigenetics is a field of research in the genetic area in which the expression of genes is studied, not only those that are inherited from the father and mother, but those that are triggered from the baby's experiences during the gestation period, arising from the experiences of the mother and that can be expressed and modify the genome. This fact can occur not only during pregnancy, but also due to the experiences of each human being, from newborn to adult. In this context, epigenetics came to break the line of reasoning that the gene is “immutable”, the factor called epigenome, which are “chemical marks” can be changed according to external factors, such as the use of drugs before and during pregnancy, stress hormones and possible traumas that generate mood disorders in vulnerable individuals and that can have hereditary effects, thus modulating gene regulation and expression. The impact of psychopathologies and maternal mood disorders and throughout life allow newborns to be psychologically vulnerable to the effects of these factors arising from the mother during development, in addition to difficult temperament, and psychiatric disorders are currently shown more frequently among women. pregnant women, increasing the risk of behavioral and mental health disorders later in the children's lives.